Design of One-Phase Inverter Using EGS002 with SPWM - Nisfa Sri Ayu Kaliky; Son Ali Akbar; Ahmad Raditya Cahya Baswara (Universitas Ahmad Dahlan, 2022)
The more advanced the development of the technological world in Indonesia, the needs of the community in the use of electrical energy are also higher so that an alternative tool is needed that can produce a voltage source such as PLN. In this thesis, a 1-phase inverter will be designed that can produce output in the form of an AC voltage of 220 volts with a frequency of 50 Hz and has a good feedback voltage so that the inverter output voltage can be stable at an AC voltage value of 220 volts. The 1-phase inverter is made using a full bridge inverter circuit, the SPWM (sinusoidal pulse width modulation) signal is generated using EGS002 by ASIC (Application Specific Integreted Circuit), and the voltage correction transformer used has a maximum working power of 600 watts. According to the results of the no-load test the 1-phase inverter can produce an AC voltage on the output side of 220 to 230 volts with 50 Hz frequencys and the results of the load test show that the inverter has a good feedback voltage so that even when the input voltage drops, the inverter output voltage value is still above 220 volts.